Characterization of the orofacial harmonization courses offered in a city in the state of Paraná (Research, Society and Development, 2021)
The objective of this work was to describe the characteristics of orofacial harmonization courses offered to dentists in a city in the Northwest region of Paraná. This is an observational, descriptive and cross-sectional study in which data were collected from information searches on websites of educational institutions, social networks and the Google platform, with the following keywords: "course" + " matching” or “facial matching” or “orofacial matching” or “botulinum toxin” or “botox” or “filling” or “hyaluronic acid”, limiting the search to a city. This resulted in 20 courses, whose therapeutic and aesthetic purposes of the procedures were included in the syllabus of 85% of the courses, while in 15% there were only aesthetic objectives. 75% of the courses were called immersion, 15% were specializations, while 10% were improvements. 85% reported working hours and, in 73.68% of these, the duration was less than or equal to five days. The amount of hours/class charged to students ranged from R$65.00 to R$1,000.00. It is concluded that the orofacial harmonization courses offered are of high value, compared to courses in other specialties, and are mostly of short duration. In addition, there was a need for the entities promoting the courses to be alerted to the adequacy of the name or type (updating, perfecting, specialization, among others) to the minimum workload required.